Fabrication of porous reaction bonded silicon carbide with multi-layered pore structures - Cho, G.-S.; Kim, G.-M.; Park, S.-W. (2009)
Reaction Bonded Silicon Carbide(RBSC) has been used for engineering ceramics due to low-temperature fabrication and near-net shape products with excellent structural properties such as thermal shock resistance, corrosion resistance and mechanical strength. Recently, attempts have been made to develop hot gas filter with gradient pore structure by RBSC to overcome weakness of commercial clay-bonded SiC filter such as low fracture toughness and low reliability. In this study a fabrication process of porous RBSC with multi-layer pore structure with gradient pore size was developed. The support layer of the RBSC with multi-layer pore structure was fabricated by conventional Si infiltration process. The intermediate and filter layers consisted of phenolic resin and fine SiC powder were prepared by dip-coating of the support RBSC in slurry of SiC and phenol resin. The temperature of 1550°C to make Si left in RBSC support layer infiltrate into dip-coated layer to produce SiC by reacting with pyro-carbon from phenol resin.
Keywords: Coated layers; Dip coating; Engineering ceramic; Fabrication process; Gradient pore; Hot gas; Low-temperature fabrication; Mechanical strength; Multi-layer pore structure; Multi-layered; Near-net shape; Phenol resin; Reaction bonded silicon carbide(RBSC); Reaction-bonded silicon carbides; Si infiltration; SiC powder; Support layer; Thermal shock resistance; Air filters; Clay; Clay minerals; Corrosion resistance; Fabrication; Fracture toughness; Mechanical properties; Phenolic resins; Phenols; Porous silicon; Resins; Silicon carbide; Structural ceramics; Pore structure